The ark and the dove : the story of Noah's wife [large type] - Smith, Jill Eileen, 1958- (Thorndike Press large print Christian fiction series., 2024)
"Zara and Noah have walked together with the Creator for their entire lives, and they have done their best in an increasingly wicked and defiant world to raise their three sons to follow in their footsteps. It has been a challenge--and it's about to get much, much harder. When the Creator tells her husband to build an ark to escape the coming wrath against the sins of humankind, Zara steps out with him in faith. But the derision and sabotage directed their way from both friends and extended family are difficult to bear, as is knowing that everyone she interacts with beyond her husband, her sons, and their wives is doomed to destruction. And when the ark is finally finished and the animals have been shut up inside, Zara and her family embark on an adventure that will test their patience and their faith as they await deliverance and dry ground."--